Regulating place : standards and the shaping of urban America - Ben-Joseph, Eran; Szold, Terry S., 1960- (Routledge, 2005)
Regulating Place looks at how design standards have shaped the built environment of urban America. Tracing the history behind the evolution of building codes, the contributors examine the increasing influence of regulatory codes over urban design and planning during the past century. From the environment to housing to public space, the volume considers the positive and negative effects of regulation on American cities - particularly the merits of flexible approaches relative to more rigid, technocratic methods. Regulating Place also questions what sort of criteria should be used to measure reg.